Isolation of cellulose from mature pods and how different bleaching agents affect its characterization - Aridi, Aida Safina; Yusof, Yus Aniza; Chin, Nyuk Ling; Ishak, Nur Akmal; Mohammad Yusof, Nor Nadiah (A S T M International, 2022)
A Fourier-transform infrared spectrometer was used to investigate the effect of using different bleaching agents during the bleaching process on the functional group of cellulose obtained from Leucaena leucocephala pods. The spectra showed that fiber treated with 5 % sodium hypochlorite (NaCIO) showed a similar functional group with the commercial cellulose. Moreover, the chemical composition analysis and whiteness index showed that fiber treated with NaCIO produced 89.37 % cellulose. The whiteness index was 78.5 %, which was the highest. Therefore, these results are expected to provide insight into the potential of utilizing L. leucocephala pods as the alternative raw material for the isolation of cellulose, as the pods of these plants are underutilized.